The effect of slope angle on propeller jet erosion near quays - Cihan, Kubilay; Ozan, Ayse Yuksel; Yuksel, Yalcin (EMERALD GROUP PUBLISHING LTD, 2012)
The problem of propeller jet-induced erosion has significantly risen during the past three decades due to an increase in the manoeuvrability of ships. Therefore, propeller-induced scours need to be considered in the design of quay structures. In this study, the effect of slope angle on propeller jet erosion was examined. Three different slope angles of m = 2.5, 2.0 and 1.5 were considered. Additionally, three different cases were considered, including an armoured layer with and without a toe apron and pile on an armoured layer with a toe apron. Flow velocity and scour measurements were performed in the experiments. For each slope angle, armour layer damage on the slope was defined by use of a damage level parameter. In addition, critical densimetric Froude numbers (Fr-d,Fr-cr) were defined for the start of damage at different slope angles.
Keywords: coastal engineering; maritime engineering; models (physical); SCOUR; PILE; Engineering; Water Resources